Creation and Characterization of the β-1,4-Glucanase (CMCase)Producing Mutant Strains of Bacillus sp. with Ultraviolet Radiation and Ethidium Bromide - Sezan, A; Baylan, M (Journal of the Hellenic Veterinary Medical Society, 2023)
In this study, the β-1,4-glucanase-producing Bacillus sp. strains were isolated from soil; then, in these strains, the undesired enzyme genes such as α-amylase, xylanase, protease were inactivated by mutation using Ethidium bromide (EtBr) and UV ray; thus, only β-1,4-glucanase producing strains were obtained. The enzyme activities (pH, temperature, thermostability, etc.) of the wild strain and its two mutant variants (UV mutant (mUV), EtBr mutant (mEB)) producing β-1,4-glucanase were partially characterized. It was found that the optimum pHs for the mUV, mEB, and the wild strain were 7.0, 6.0 and 9.0, respectively; and the optimum temperatures were 50, 60, and 50 ℃, respectively. Finally, the molecular weights of the cellulase enzymes of all the three bacteria were found to be 40 kDa by SDS-PAGE and zymogram analysis.